Back to Basics: Recognition of Sepsis with New Definition - Horak, Jan; Martinkova, Vendula; Radej, Jaroslav; Matejovič, Martin (Journal of clinical medicine, 2019)
Patients with serious infections at risk of deterioration represent highly challenging clinical situations, and in particular for junior doctors. A comprehensive clinical examination that integrates the assessment of vital signs, hemodynamics, and peripheral perfusion into clinical decision making is key to responding promptly and effectively to evolving acute medical illnesses, such as sepsis or septic shock. Against this background, the new concept of sepsis definition may provide a useful link between junior doctors and consultant decision making. The purpose of this article is to introduce the updated definition of sepsis and suggest its practical implications, with particular emphasis on integrative clinical assessment, allowing for the rapid identification of patients who are at risk of further deterioration.
Keywords: infection; septic shock; definition; risk assessment; early recognition of sepsis; sepsis